Comparison of high-dose versus low-dose oxytocin regimen for induction and augmentation of labour. (18th April 2012) - O'Connor, HD; Hehire, MP; Doyle, A; Coulter-Smith, S; Breathnach, FM
Abstract : The use of oxytocin for induction and augmentation of labour is a major component in the active management of labour. Its use is associated with lower caesarean section rates however it carries potential for uterine hyperstimulation/tachysystole and fetal compromise. We sought to compare the standard 'high-dose' regimen employed in the Rotunda hospital until July2010 with a lower dose regimen. The regimen of oxytocin for induction/augmentation of primigravid labour changed on 1/07/2010 to a 'low-dose' regimen commonly employed internationally. We prospectively recorded maternal characteristics and perinatal outcomes among primiparous women exposed to the'low-dose' regimen (September2010) and those exposed to the high-dose regimen in June2010. 116 primiparous women received the high-dose oxytocin regimen. 143 women received the low-dose regimen. Maternal characteristics (maternal age, gestation or induced labour rates) were similar in the two cohorts. There was no significant difference in duration of the 1 st stage of labour. A decreased incidence of uterine hyperstimulation was observed in women exposed to the low-dose regimen (8.4vs46.6%, p<0.0001). The low-dose regimen was also associated with a statistically significant reduction in the duration of the second stage of labour. Although a trend was observed toward an increased caesarean delivery rate with the lower dose regimen, this did not achieve statistical significance (20.3vs16.4%, p=0.4218). Rates of NICU admission, instrumental delivery or anal sphincter injury were similar in both groups. Our findings suggest a low-dose oxytocin regimen is associated with decreased uterine hyperstimulation and decreased duration of the second stage of labour. Mode of delivery and perinatal outcome were unaffected.